PENYUTRADARAAN DENGAN GAYA INTERAKTIF DALAM PRODUKSI KARYA FEATURE “PIJAR ISLAM EPISODE MASJID JOGOKARIYAN” - Gilang Nursalam; Hans Hermang Mintana; Wahyu Sudarmawan (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACT Mosques are not only places used for ritual worship, but also as a means for carrying out social activities, education, and as a means of strengthening social interaction in society. The Jogokariyan Mosque, located in Mantrijeron District, Jogjakarta City, has successfully transformed into a mosque that is famous for its good and innovative management and programs, especially during the month of Ramadan where there is the Jogokariyan Ramadhan Village Festival. This content is suitable to be presented in an audio-visual work in feature format. This feature work entitled "Pijar Islam Jogokaryan Mosque episode" tells about the presenter's journey to visit the Jogokariyan Mosque which is famous for its good and innovative programs. Viewers are invited to tour the Jogokariyan Mosque directly from interviews with sources. This work is included as a seasonal feature because it is presented for the Ramadhan program with a duration of 24 minutes. In this feature, the director has control over all technical and creative aspects by using an interactive approach, where interviews are the main thing to build the storyline. Interaction is not only carried out with sources, but also with viewers at home. The results of this audio visual work will show the beauty of the natural landscape, human interest, architecture and diverse ornaments in Yogyakarta with an Islamic pattern. It is hoped that this will lead to an atmosphere of a religious journey that is full of beauty and is expected to provide a complete picture in accordance with the director's wishes. Keywords: Feature, Director, Interactive, Jogokariyan Mosque.